Effect of microclimate on body temperature of black and white coloured breeds of goat (Indian Journal of Animal Production and Management, 2018)
The present experiment was carried out to compare the effect of microclimate on rectal temperature (RT)  and body surface temperature (BST) of black and white indigenous breeds of goat. Diurnal variation of  ambient temperature (AT) and relative humidity (RH) were recorded at hourly intervals inside goat pen  and temperature humidity index (THI) was calculated. The RT and BST (fore head, back, rump, flank, hind  cannon, udder and chest) were monitored twice a day (morning and afternoon) at fortnightly intervals in  twelve female goats (6 each of black and white body coat coloured breed). The mean AT, RH and THI of  pens were 24.86±0.98 ºC (ranged from 18.3 to 33.3 ºC), 51.06±2.51% (ranged from 30.4 to 70.9%) and  71.14±1.00 (ranged from 63.9 to 78.8), respectively. The RT and BST at fore head, back, rump, flank,  hind cannon and chest regions increased significantly from morning to afternoon (P
Keywords: Body surface temperature; Coat colour; Goats; Rectal temperature